Influence of synthetic pathway, molecular weight and side chains on properties of indacenodithiophene-benzothiadiazole copolymers made by direct arylation polycondensation. Issue 13 (22nd March 2021) - Adamczak, Desiree; Perinot, Andrea; Komber, Hartmut; Illy, Anna; Hultmark, Sandra; Passarella, Bianca; Tan, Wen Liang; Hutsch, Sebastian; Becker-Koch, David; Rapley, Charlotte; Scaccabarozzi, Alberto D.; Heeney, Martin; et al.
Abstract : Poly(indacenodithiophene- alt -benzothiadiazole) with different side chains and molecular weight is made using two different pathways in which all C–C coupling steps are achieved by C–H activation, and the products are comprehensively investigated. Abstract : Atom-economic protocols for the synthesis of poly(indacenodithiophene- alt -benzothiadiazole) (PIDTBT) are presented in which all C–C coupling steps are achieved by direct arylation. Using two different synthetic pathways, PIDTBT copolymers with different side chains (hexylphenyl, octylphenyl, dodecyl, methyl/2-octyldodecylphenyl, 2-octyldodecylphenyl/2-octyldodecylphenyl) and molecular weight (MW) are prepared. Route A makes use of direct arylation polycondensation (DAP) of indacenodithiophene (IDT) and 4, 7-dibromo-2, 1, 3-benzothiadiazole (BTBr2 ) leading to PIDTBT in high yields, with adjustable MW and without indications for structural defects. Route B starts from a polyketone precursor also prepared by DAP following cyclization. While route B allows introduction of asymmetric side chains at the IDT unit, polymer analogous cyclization gives rise to defect formation. The absorption coefficient of PIDTBT with alkylphenyl side chains made by route A increases with MW. Field-effect hole mobilities around ∼10 −2 cm 2 V −1 s −1 are molecular weight-independent, which is ascribed to a largely amorphous thin film morphology. PIDTBT with linear dodecyl side (C12) chains exhibits a bathochromic shift (20 nm), in agreement with theory, and more pronounced vibronic contributions to absorption spectra. In comparison to alkylphenyl side chains, C12 side chains allow for increased order in thin films, a weak melting endotherm and lower energetic disorder, which altogether explain substantially higher field-effect hole mobilities of ∼ 10 −1 cm 2 V −1 s −1 .